2018
DOI: 10.1039/c8nr05239e
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of metal organic framework-derived FeS2 hollow nanocages@reduced graphene oxide for K-ion storage

Abstract: We are the first to utilize reduced graphene oxide (RGO) wrapped metal organic framework-derived FeS2 hollow nanocages (FeS2@RGO) as an anode for K-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 54 publications
3
100
0
Order By: Relevance
“…All the electrodes use DME-KFSI as electrolyte at 100 mAh g −1 for measurement. [24,25,[44][45][46][47][48][49][50][51] It is found that our Sb 2 O 3 -RGO composite shows a better K-ion storage performance than other metallic oxide-based materials for KIBs. Compared with Sb 2 O 3 electrode, RGO electrode exhibits the initial reversible specific capacity of 207 mAh g −1 and maintains a reversible specific capacity of 208 mAh g −1 after 50 cycles, owning to its excellent stability and conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…All the electrodes use DME-KFSI as electrolyte at 100 mAh g −1 for measurement. [24,25,[44][45][46][47][48][49][50][51] It is found that our Sb 2 O 3 -RGO composite shows a better K-ion storage performance than other metallic oxide-based materials for KIBs. Compared with Sb 2 O 3 electrode, RGO electrode exhibits the initial reversible specific capacity of 207 mAh g −1 and maintains a reversible specific capacity of 208 mAh g −1 after 50 cycles, owning to its excellent stability and conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…[43] Impressively fast potassium-ion storage performance is evident in our system when compared to the rate performance of previously reported advanced anode materials (Figure 6d). [15,[18][19][20]27,39,[44][45][46][47][48][49] To further verify the cycle life of our electrode,t he long-term cycling performance of NCS@RGO-2 using KFSI-EP electrolyte at 200 mA g À1 was ascertained (Figure 6e). Our NCS@RGO-2 electrode exhibits an excellent cycle stability of 495 mAh g À1 at 200 mA g À1 after 1900 cycles (cycling for 314 days).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[14,15] However,c arbonaceous materials exhibit ar elatively low reversible capacity because potassium-ion storage is limited by the insertion mechanism. [18] Liu et al constructed thinly layered antimony sulfide/carbon sheet composites by solution-triggered one-step shear exfoliation, to produce an electrode with ah igh potassium-ion storage capacity (404 mAh g À1 at 500 mA g À1 after 200 cycles). [18] Liu et al constructed thinly layered antimony sulfide/carbon sheet composites by solution-triggered one-step shear exfoliation, to produce an electrode with ah igh potassium-ion storage capacity (404 mAh g À1 at 500 mA g À1 after 200 cycles).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] The physical andc hemical properties of potassium and lithium are also very similar.A dditionally,t he standard electrochemical potential of K( À2.93 V) is very close to that of Li (À3.04 V) with respect to the standard hydrogen electrode (SHE). [10][11][12][13][14][15][16][17][18][19][20] Amongt hem, only af ew transition metal oxides, such as Co 3 O 4 -Fe 2 O 3 , [18] a-MoO 3 , [21] SnO 2 , [22,23] and V 2 O 3 [24] have been investigated in KIBs. [10][11][12][13][14][15][16][17][18][19][20] Amongt hem, only af ew transition metal oxides, such as Co 3 O 4 -Fe 2 O 3 , [18] a-MoO 3 , [21] SnO 2 , [22,23] and V 2 O 3 [24] have been investigated in KIBs.…”
Section: Introductionmentioning
confidence: 99%